Genetic resources program = Programa de recursos genéticos - Debouck, Daniel G.; Aranzales Rondón, Ericson; Balcázar, María del Socorro; Ciprián, Arsenio; Cuervo Ibáñez, Maritza; Hernández, Ángela Marcela; Mafla, G.; Martínez, Josefina; Ocampo Nahar, César H.; Santos, Luís Guillermo; Toro Chica, Orlando (International Center for Tropical Agriculture, 2010)
Plant genetic resources for food and agriculture form the basis of global food security. They comprise a diversity of genetic materials contained in traditional varieties, modern cultivars, and wild relatives. CIAT’s Genetic Resources Program hosts the world’s largest genetic holdings of beans (close to 36,000 materials), cassava (over 6,000), and tropical forages (over 21,000), obtained or collected from over 141 countries. They are kept and maintained under an agreement with the International Treaty on Plant Genetic Resources for Food and Agriculture of the Food and Agriculture Organization of the United Nations (FAO).